If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25(x + -3) = 12(x + 2) + -10 Reorder the terms: 25(-3 + x) = 12(x + 2) + -10 (-3 * 25 + x * 25) = 12(x + 2) + -10 (-75 + 25x) = 12(x + 2) + -10 Reorder the terms: -75 + 25x = 12(2 + x) + -10 -75 + 25x = (2 * 12 + x * 12) + -10 -75 + 25x = (24 + 12x) + -10 Reorder the terms: -75 + 25x = 24 + -10 + 12x Combine like terms: 24 + -10 = 14 -75 + 25x = 14 + 12x Solving -75 + 25x = 14 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -75 + 25x + -12x = 14 + 12x + -12x Combine like terms: 25x + -12x = 13x -75 + 13x = 14 + 12x + -12x Combine like terms: 12x + -12x = 0 -75 + 13x = 14 + 0 -75 + 13x = 14 Add '75' to each side of the equation. -75 + 75 + 13x = 14 + 75 Combine like terms: -75 + 75 = 0 0 + 13x = 14 + 75 13x = 14 + 75 Combine like terms: 14 + 75 = 89 13x = 89 Divide each side by '13'. x = 6.846153846 Simplifying x = 6.846153846
| -6=x-13 | | 12x+15=180 | | 33-15y=-12 | | 3[4x+6]=24 | | -x+5=-10 | | 500=45c+35(12-c) | | 500=45c+35(12+c) | | 22t+45=-65 | | 4(6+x-5)=x-3 | | 8d-2=-34 | | x^3-7x+21=0 | | 4x^2+24x-20= | | 99=-3(1-6x)-x | | 950.00.08= | | 4x^2+24x+20= | | -2(x-3)+5x=9x-5 | | 4(6+x-5)=3-x | | 3(22-5)=2z+13 | | 4y+6y=90 | | 100xq=1.1387 | | -2+n=9 | | -6/5-(-3/2)= | | 2.8-10m=8.19 | | 3(a-5)=6a-(3a+15) | | 2v+5v-8=18 | | 3xy+6=p | | 4(6+x)-5=3-x | | 4(2-1)=-8(0.5-y) | | (8x+8)(4x^2+3x+5)= | | c^30+275=1225 | | =-12-8x-3/4 | | X^4-x^3-29x^2-x-30=0 |